Polyelectrolyte complex‐based thermochromic hydrogels containing carbonized polymer dots for smart windows with fast response, excellent solar modulation ability, and high durability - Yuting Wang; Xu Fang; Siheng Li; Ni An; Hongyu Pan; Junqi Sun (SmartMat, 2024)
Abstract Thermochromic smart windows have gained increasing popularity in light modulation and energy management in buildings. However, the fabrication of flexible thermochromic smart windows with high luminous transmittance (Tlum), tailorable critical temperature (τc), strong solar modulation ability (ΔTsol), and long‐term durability remains a huge challenge. In this study, hydrogel‐based thermochromic smart windows are fabricated by sandwiching thermochromic hydrogels of polyallylamine hydrochloride, polyacrylic acid, and carbonized polymer dots (CPDs) complexes between two pieces of transparent substrates. Benefiting from the incorporation of nanosized CPDs, the thermochromic hydrogel has an ultrahigh Tlum of ~98.7%, a desirable τc of ~24.2 °C, a ΔTsol of ~89.3% and a rapid transition time of ~3 s from opaque state to transparent state. Moreover, the thermochromic hydrogel exhibits excellent anti‐freezing ability, tight adhesion toward various substrates, and excellent self‐healing capability. The self‐healing capability enables the fabrication of large‐area smart windows by welding multiple hydrogel pieces. The smart windows retain their original thermochromic properties after being stored under ambient conditions for at least 147 days or undergoing 10,000 uninterrupted heating/cooling cycles. The model houses with smart windows can achieve a temperature reduction of 9.2 °C, demonstrating the excellent indoor temperature modulation performance of the smart windows.